PERANCANGAN SISTEM INFORMASI TABUNGAN SISWA PADA SD NEGERI 1 CANDI BERBASIS WEB METODE PROTOTYPE - Dede Permana (OKTAL : Jurnal Ilmu Komputer dan Sains, 2024)
Currently, to achieve a fast and accurate information can not be separated from the information system that is built well. Likewise with the student savings information system. The large number of savers every day and the frequent occurrence of damage to the passbook at SD Negeri 1 Candi make users find it difficult to manage data because the data must be reprocessed, also at the time of making reports, besides that users have difficulty when searching. The method used itself is a process prototype method that allows developers to create a software model, this method is best used if the client cannot provide maximum information about the needs he wants. In making the StudentSavings Information System, the system requires data to be processed so as to produce information that is in accordance with what is needed. Some of the information needed by the homeroom teacher is information on student savings as a result of verification that comes from student data, other information is the result of a search process in the field. With the proposed system, there are no longer obstacles for Class Teachers in processing student savings reports and finding information about required student savings. The system also makes it easy for users (Class Teachers) when making reports, because the data that comes in every day is automatically recorded in the database.